An alkali-ion insertion approach to structurally transform metal–organic frameworks. Issue 40 (23rd September 2016) - Hu, Yue-Qiao; Li, Mu-Qing; Li, Teng; Wang, Yan-Yan; Zheng, Zhiping; Zheng, Yan-Zhen
Abstract : Insertion of alkali metal ions into heterometallic 3d–4f metal–organic frameworks (MOFs) leads to new MOFs whose structures are sensitively dependent on the size of the alkali ions used and with significantly enhanced effective free crystallographic volume. Abstract : The insertion of alkali metal ions into a prevalent lanthanide-carboxylate coordination motif in heterometallic 3d–4f metal–organic frameworks (MOFs) leads to new MOFs whose structures are sensitively dependent on the size of the alkali ions used and with significantly enhanced effective free crystallographic volume.